2016
DOI: 10.25215/0304.104
|View full text |Cite
|
Sign up to set email alerts
|

Hope and Psychological Well Being among Diabetes Patients: A Correlational Study

Abstract: Hope is an optimism that is experienced even though the individual may have little personal control over the situation. This nature of hope changes the behaviour of patients and these changes influence various aspect of personality psychological well-being of patients and make their behaviour somewhat positive towards their disease to cope with it. One’s capacity to hope for things places an absolute limit on one’s power. Thus, Adult hope of patients helps them to deal with their disease in a positive manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Additionally, the results found statistically signi cant differences in PWB in favor of females. This result is consistent with previous studies [34,38,39,40] that found statistically signi cant differences in PWB in favor of females. However, it is not consistent with the results of studies [41,42] which did not nd statistically signi cant differences in PWB due to the gender variable.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, the results found statistically signi cant differences in PWB in favor of females. This result is consistent with previous studies [34,38,39,40] that found statistically signi cant differences in PWB in favor of females. However, it is not consistent with the results of studies [41,42] which did not nd statistically signi cant differences in PWB due to the gender variable.…”
Section: Discussionsupporting
confidence: 94%
“…Hope directly affected PW in the study subjects. Accordingly, Nabi et al (2016) observed a significant positive relationship between hope and PW in patients with diabetes. Schroevers et al (2011) found that cancer patients who can think about pleasant things, instead of negative experiences of cancer, are healthier than others.…”
Section: Perceived Social Supportmentioning
confidence: 86%